Clouds in the perturbed climate system : their relationship to energy balance, atmospheric dynamics, and precipitation - Heintzenberg, J. (Jost); Charlson, Robert J. (Strüngmann Forum reports., 2009)
Here, experts consider the many roles that clouds play in the changing climate - one of the least understood and most puzzling aspects of atmospheric science.